Contextualizing Islamic Education in the Digital Era: Social Media Integration Strategies in Learning Islamic Materials - Darain, A. Sa’dud; Maimun, Maimun (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study analyzes the contextualization strategy of Islamic Religious Education learning at the Nahdlatut Ta'miliyah Islamic Boarding School through the use of social media and its role in enhancing community religious understanding. Employing a qualitative approach with a case study design, data were collected through observation of social media content, in-depth interviews with pesantren caretakers and administrators, and analysis of audience interactions on digital platforms. The findings reveal that social media particularly YouTube and Instagram functions as a primary infrastructure for da‘wah and learning rather than merely a supplementary medium. Classical Islamic texts (yellow books) are presented in a communicative, applicable, and contextual format, reflecting efforts to preserve the authenticity of traditional Islamic scholarship while adapting it to contemporary social, cultural, and technological contexts. The learning strategy emphasizes the use of everyday life examples, humor, and two-way interaction, aligning with the principles of Contextual Teaching and Learning (CTL) and Islamic educational psychology. This approach effectively increases audience engagement and strengthens the understanding and internalization of Islamic values. Furthermore, social media provides a dialogical space that enables direct feedback, allowing pesantren to adjust da‘wah content to actual community needs. Nonetheless, the study identifies challenges related to maintaining a balance between contextualization and theoretical depth, as well as the need to diversify content formats to reach broader and younger audiences. Overall, the study confirms that social media-based contextualization of Islamic education requires pedagogical competence, media literacy, and contextual sensitivity to ensure relevance and impact in the digital era.